Analysis of Onstage Acoustics Preference of Musicians of Traditional Performance of Javanese Gamelan Based on Normalized Autocorrelation Function - Suyatno, Suyatno; Tjokronegoro, Harijono A.; Merthayasa, I Gede Nyoman; Supanggah, Rahayu (Journal of Engineering and Technological Sciences, 2016)
On-stage sound field analysis of a traditional performance of the Javanese gamelan at Pendopo ISI Surakarta, Indonesia was conducted by analyzing the effective decay time of a normalized autocorrelation function called tau-e, Ïe , during a performance of the Gambyong Pare Anom dance. The parameter tau-e is used to describe the richness of the frequency content, tempo, and types of gamelan instruments being played at a certain time and position on stage. The tau-e parameter is important for musicians in order to maintain communication between each other such that they can keep the performance in harmony. In order to determine the acoustic parameters heard by gamelan musicians on stage, sound measurements were conducted at 4 points on stage during a performance. Each position represents a specific group of gamelan instruments, which have different characteristics of loudness and frequency, different functions and different ways the instruments are played. The analysis showed that each of the four positions had a different value ofÂ Ïe , which fluctuated throughout the performance. Overall, the dominantÂ Ïe at position 1 was 20 ms; at position 2 it was 50 ms; at position 3 it was 20 ms; and at position 4 it was 40 ms. The distribution ofÂ Ïe on the stage shows that positions 1 and 3 had more frequency richness compared to positions 2 and 4.